Operational Efficiency and Cost-Benefit Analysis of Electronic Medical Records (EMR) Transformation at the MAS Clinic in South Kalimantan - Novia Purnamasari; Martin Agusta; Adhika Ramadhan; Herman S. Soegoto; Agus Riyanto (Golden Ratio of Mapping Idea and Literature Format, 2026)
Digital transformation in the healthcare sector has become a strategic approach to improving operational efficiency and service quality. One form of this transformation is the implementation of Electronic Medical Records (EMR), which enables faster, more accurate, and integrated patient data management. Clinic MAS in South Kalimantan adopted EMR to replace the conventional administrative system that previously caused queue build-ups, service delays, potential errors in prescription reading, high administrative burdens, and weak operational control. This study aims to analyze the operational efficiency and cost-benefit of EMR transformation at Clinic MAS from the perspective of Digital Analytics in Business. The research employs a qualitative descriptive approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving the clinic director, administrative staff, and healthcare workers. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results show that EMR implementation has eliminated queue build-ups, minimized prescription errors, reduced fraud potential, reduced paper usage through a paperless system, and lowered operational costs. Furthermore, EMR has increased clinic revenue by 60% to 70% within one year and enabled real-time business monitoring. The findings confirm that EMR transformation serves not merely as an administrative innovation but as a digital business intelligence strategy that supports profitability, business efficiency, and clinic competitiveness in the digital era.